Solve for the equation:log_4 x+log_4(x+6)=2

  1. Which of the following options rewrites log_4(9m^3/n)Quotient Rule of Logarithms, the Product Rule of Logarithms, and the Power
    1. answers icon 1 answer
    2. …. asked by ….
    3. views icon 67 views
  2. Which of the following options rewrites log_4(9m^3/n)Quotient Rule of Logarithms, the Product Rule of Logarithms, and the Power
    1. answers icon 1 answer
    2. …. asked by ….
    3. views icon 72 views
  3. Q: Prove- 2/log_8a - 4/log_2a= 1/log_4ai tried dividing 1/log_4a by 2/log_4(8) - 1/log_4a by 4/log_4(2) to get log_4(8)/2.log_4a
    1. answers icon 1 answer
    2. Anonymous asked by Anonymous
    3. views icon 362 views
  4. Solve for the equation:log_4 x+log_4(x+6)=2
    1. answers icon 1 answer
    2. views icon 70 views
  5. Select the correct answer.What is the solution set to this equation? log_4 (x-3) + log_4 (x+3) = 2 A. x = -16 and x = 16 B. x =
    1. answers icon 1 answer
    2. willie asked by willie
    3. views icon 52 views
  6. Match each equation with an equivalent equation on below.Some answer options on the right will not be used. log_2(64)=6
    1. answers icon 1 answer
    2. views icon 50 views
  7. log_5[log_4(log_3(x))] = 1log_5 = log with the base of 5 log_4 = log with the base of 4 log_3 = log with the base of 3 Answer:
    1. answers icon 1 answer
    2. Anonymous asked by Anonymous
    3. views icon 1,224 views
  8. Solve the following logarithmic equation for x.log_4(2x-8)=log_5(4x-10)
    1. answers icon 1 answer
    2. views icon 55 views
  9. find the inverse.f(x)=-2+log_4(x-4)
    1. answers icon 0 answers
    2. brad asked by brad
    3. views icon 325 views
  10. Prove.3/(log_2 (a)) - 2/(log_4 (a)) = 1/(log_(1/2)(a))
    1. answers icon 0 answers
    2. Hasane asked by Hasane
    3. views icon 389 views